Discriminatory Tax Burden: An Implication of Differences in Methods and Rates of Depreciation in Present Income Tax Act - Kandel, Puspa (Tribhuvan University Journal, 2011)
Available with full text. Key words: Tax Burden; Income Tax Act; Nepal Tribhuvan University Journal Vol XXIII, No. 1, 2001 Page: 97-110 Uploaded date: 21 April, 2011